ASSESSMENT OF AWARENESS AND COMPLIANCE OF ONLINE SELLERS’ ON ONLINE TAXATION POLICY IN METRO MANILA, PHILIPPINES - ap, Renato E. Apa (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of the study is to determine the level of awareness and degree of compliance of online sellers’ regarding on their obligation to pay taxes. The data utilized on this study were the responses of 400 randomly selected online sellers’ in Metro Manila, Philippines as respondents through a questionnaire. The data gathered from the respondents were summarized and analyzed using descriptive statistics in profiling them as well their awareness and compliance on taxation. A correlational technique was explored also to see if there is significant relationship between respondents’ awareness and compliance on taxation. All data were analyzed using Statistical Software for accuracy of computations. Results shows that most of the respondents age were surprisingly below 20 years old, dominated by female, undergraduate, single, less than a year in the business and monthly income derived from the business is less than Php5,000.00. In terms of awareness the respondents are moderately aware of their obligation as manifested on their average weighted mean of 3.008. And in terms of degree of compliance, most of the respondents much agree as revealed on their average weighted mean of 3.491. Their level of awareness and degree of compliance are significantly related based on computed p-value which is less than the significant level of 0.05. Results from study helps the government to intensify its awareness campaign and compliance of online business on paying tax and crack new policy on online taxation monitoring since one of the government components in generating revenue is on sales tax. Applying this study in other cities as well as in the whole country may assembled more information for decision making in the government.